Issues of implementation of international legal norms in the field of migration into the national legal system of the Republic of Azerbaijan - N. Zeynalova-Sultanova (Науковий вісник Ужгородського національного університету. Серія Право)
It is indicated оne of the scientific paradigms of modern international law, which has theoretical and practical significance, are issues related to the national legal implementation of international legal norms. Considering that the norms of international law related to migration arose as a need of our time, the importance of implementing this category of legal norms in national law becomes more obvious. In this context, the national legal implementation of international legal norms in the field of migration has both theoretical and practical significance. The increase in the number of international treaties in this area requires the inclusion of the provisions of “these international treaties in national legislation”.